On the Low Frequency Pressure Fluctuation in a 3/4 Open Jet Automotive Wind Tunnel - Q. Jia; Y. Zhu; D. Bao; M. M. Rashidi; Z. Yang (Journal of Applied Fluid Mechanics, 2019)
In the present research, a possible generation mechanism of low-frequency buffeting phenomenon based on a 1:15 open jet automotive wind tunnel was investigated. Evolution of vortex structures and pressure field in the plenum chamber have been visualized and analyzed by Large-eddy simulation (LES). It is shown that the low frequency pressure fluctuation is caused by the large-scale structures and their interaction. Multiple proper orthogonal decomposition was adopted to analyze the flow field in the plenum chamber. The characteristic frequencies of the vortex-rings after pairing is the same as the dominant resonance of buffeting at this wind velocity.